The genus Senna Mill. (Leguminosae: Caesalpinioideae) in a fragment of the Ecological Station Raso da Catarina, Bahia, Brazil (Acta Scientiarum. Biological Sciences, 2017)
Senna comprises about 300 species with circuntropical distribution, widely represented in the Americas, also occurring in Africa, Australia, Asia and Oceania. The Brazil includes 80 species, of which 27 are endemic, 50 reported from Bahia and 22 recorded from the Caatinga. The floristic survey of Senna in the Ecological Station Raso da Catarina included analysis of specimens collected March 2010 to October 2011. The analyses were supplemented with dried collections from the following herbaria: ALCB, EAC, HRB, HUEFS and MBM. Seven taxa were recorded. The most representative taxa in the area were Senna rizzinii H.S.Irwin & Barneby and S. acuruensis (Benth.) H.S.Irwin & Barneby var. acuruensis. The genus can be found in a variety of environments from preserved to degraded areas and in sandy, sandy-clayey or rocky soils. The taxonomic treatment includes anidentification key, descriptions, illustrations, photos, data of the geographical distribution, reproductive phenology and comments about the taxa.